PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SD NEGERI 016 BUKIT TIMAH KECAMATAN DUMAI SELATAN - Arman Syah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study is based on the learning outcomes of social studies students of grades VI SD Negeri 016 Bukit TimahKecamatan Dumai Selatan Kota Dumai is still very low. This study aims to improve social studies learningoutcomes. From the data analysis, there is an increase of both teacher activity, student activity, and studentlearning result, that is teacher activity at meeting 1 cycle I percentage is 58,3% (enough) and at the secondmeeting increased to 70,8% (good). In cycle II the third meeting of teacher activity value from 70,8% (good) to83,4% (very good) and at the fourth meeting increased to 95,8% (very good). Judging from the activity ofstudents also experienced an increase from 54,2% (enough) to 62,5% (good). In the second cycle of the thirdmeeting to be 79,2% (good) and at the fourth meeting increased to 91,7% (very good). Judging from the resultsof the students also experienced increase from the average score of students on the basic score of 55.25 after thefirst cycle the average student score increased to 73,75 with an increase of 18,5 points from the baseline score.In the second cycle student learning outcomes also experienced an increase of 12 points from cycle I withaverage student scores 85,75. From the data analysis there is an increase both from teacher activity, studentactivity, and student learning outcomes. It can be concluded that the advancement of model Numbered HeadsTogether (NHT), can improve the learning outcomes of social studies learning outcomes of class VI SD Negeri016 Bukit Timah Kecamatan Dumai Selatan Kota Dumai.